The effect of sildenafil, a phosphodiesterase-5 inhibitor, on acetic acid-induced colonic inflammation in the rat - ERCAN, FERİHA; YÜKSEL, MERAL; ALİCAN, YAŞAR İNCİ (WILEY, 2009)
Sildenafil, a selective and potent inhibitor of cyclic guanosine monophosphate (cGMP)-specific phosphodiesterase (PDE)5, has a relaxant effect on the smooth muscle cells of the arterioles supplying the human corpus cavernosum acting via nitric oxide (NO)-dependent mechanism. This study aimed to investigate the possible protective effect of sildenafil citrate on the extent of tissue integrity, oxidant-antioxidant status and neutrophil infiltration to the inflamed organ in a rat model of acetic acid-induced colitis. Colitis was induced by intrarectal administration of 1 mL of 5% acetic acid to Sprague-Dawley rats (200-250 g; n = 7-8/group). Control rats received an equal volume of saline intrarectally. In treatment groups, the rats were treated with either sildenafil citrate (5 mg/kg/day; subcutaneously) or saline for 3 days. After decapitation, distal colon was weighed and scored macroscopically and microscopically. Tissue samples were used for the measurement of malondialdehyde (MDA) and glutathione (GSH) levels, myeloperoxidase (MPO) activity, and oxidant production. Trunk blood was collected for the assessment of serum tumor necrosis factor (TNF)-alpha and interleukin (IL)-1 beta levels. In the colitis group, the colonic tissue was characterized by lesions, increased lipid peroxidation with a concomitant reduction in GSH content, increased MPO activity and oxidant production. Serum TNF-alpha and IL-1 beta levels were higher in the colitis group compared to control values. Sildenafil reversed these inflammatory parameters nearly back to control values. Sildenafil citrate administration to rats with acetic acid-induced colitis seems to be beneficial via prevention of lipid peroxidation, oxidant generation, cytokine production and neutrophil accumulation.
Keywords: colitis; inflammation; phosphodiesterase; rat; reactive oxygen metabolites; sildenafil citrate; REACTIVE OXYGEN; COLITIS; MODULATION; ARGININE